Germany : Financial Sector Assessment Program-Stress Testing the Banking and Insurance Sectors-Technical Notes. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2016)
This paper assesses Germany's financial system and, in particular, its potential for spillover risk. The analysis comprises structural and financial statement analyses, detailed stress tests for banks and insurance companies, and spillover risk analysis. Solvency and liquidity stress tests cover all 1,776 banks operating in Germany, and insurance-sector analysis covers 93 percent of the life insurance sector in terms of the assets. Germany is highly interconnected through trade and financial channels. The total consolidated claims of German banks on foreign banks, nonbank private sector, and public sector stood at about USD 1.7 trillion in the second quarter of 2015, with the majority of cross-border exposures vis-a-vis France, Italy, the United Kingdom, and the United States.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet